Developing oral health services for people experiencing severe and multiple disadvantage: a case study from Southwest England - Paisi, Martha; Withers, Lyndsey; Anderson, Rebecca; Doughty, Janine; Griffiths, Lisa; Jameson, Ben; Murphy, Elizabeth; Musa, Afsha; Nelder, Abigail; Rogers, Shona; Witton, Robert (Frontiers in Oral Health, 2024)
People experiencing severe and multiple disadvantage (SMD) have disproportionately high levels of dental disease and tooth loss but have limited access to dental care. This paper presents an evidence-based case study of co-designing, implementing, evaluating and refining a community dental clinic for people experiencing SMD in the Southwest of England. It shares challenges, lessons, and solutions. Tailored interventions that coordinate flexible and responsive care are important for facilitating dental access for individuals experiencing SMD. Participatory approaches can deliver a range of impacts both on research and service development. No single fixed model of co-design can be applied in service development, and the choice will vary depending on local context, available resources and joint decision making. Through co-design, vulnerable populations such as those with SMD can shape dental services that are more acceptable, appropriate and responsive to their needs. This approach can also ensure long-term sustainability by bridging treatment pathway development and commissioning.